Dietary oleic acid-induced CD36 promotes cervical cancer cell growth and metastasis via up-regulation Src/ERK pathway. (1st December 2018) - Yang, Ping; Su, Chunxiao; Luo, Xuan; Zeng, Han; Zhao, Lei; Wei, Li; Zhang, Xiaoyu; Varghese, Zac; Moorhead, John F.; Chen, Yaxi; Ruan, Xiong Z.
Abstract: Epidemiological and experimental studies have revealed strong associations between dietary lipids and cancer risk. However, the molecular mechanisms underlying the effects of dietary fatty acids on the genesis and progression of cancer have been poorly explored. In this study, we found that a high olive oil diet stimulated cervical cancer (CC) carcinogenesis, and oleic acid (OA), the main lipid in olive oil, was associated with increased malignancy in HeLa cells. OA up-regulated the expression of CD36, which is the best characterized fatty acid transporter. Inhibiting CD36 prevented the tumor-promoting effects of OA, while overexpressing CD36 mimicked the effects of OA. Clinically, CD36 expression was positively correlated with tumor progression and poor prognosis in patients with CC. Furthermore, OA induced Src kinase and downstream ERK1/2 pathway activation in a CD36-dependent manner. Pretreatment of HeLa cells with an Src kinase inhibitor largely blocked the tumor-promoting effect of OA. Our findings suggest that dietary OA exerts a stimulatory effect on CC growth and metastasis, and CD36 might be a promising therapeutic target that acts against CC through an Src/ERK-dependent signaling pathway. Highlights: Dietary oleic acid promotes the tumorgenesis of cervical cancer (CC) in vivo. Oleic acid stimulates HeLa cell proliferation, migration, and invasion in vitro. The fatty acid receptor CD36 plays a key role in oleic acid induced tumor-enhancing effects. High CD36 expression induced by oleic acid may initiates intracellular signaling through Src to promote CC development.